A dissertation submitted as a partial fulfilment for the degree of Magister in “Literary Stylistics and Discourse Analysis” - Imene Moulati (My University, 2015)
My dissertation will examine how discourse in Paul Auster’s novel City of Glass (1985) engages with Carl Jung’s theory of Archetypes and Individuation. I argue that archetypal features are essentially implicated in the dialogical interactions in City of Glass; wherein a variety of discourse strategies are employed to personify different Jungian archetypes through the novel’s characters. I further argue that the psychological journey of the protagonist Daniel Quinn is an implicit representation of Auster’s process of psychic individuation displayed through the novel’s narrative structure. I will implement Halliday’s Systemic Functional Linguistics (SFL) as a framework for analysis of discourse in City of Glass; thereby revealing the archetypal nature of the different characters, and the individuation function as realized in the plot structure. The first chapter will set out the theoretical background and the review of literature for the research. I will provide a clear account of the Jungian theory of Archetypes and Individuation, and a concise description of Systemic Functional Linguistics. The second chapter will be an employment of the Hallidayan’s constructs of Register to introduce Auster’s City of Glass within a defined context. Chapter Three will be a systemic discourse analysis of the novel with regard to Jungian psychology. I will identify the semantic and the lexico-grammatical features pertaining to the realization of specific archetypes and individuation process in the narrative. Finally, I will conclude with a mapping of the patterns: character/archetype and plot structure/individuation in City of Glass